The descending branch of the lateral femoral circumflex artery is a good option in CABG with arterial grafts - Gaiotto,Fábio Antonio (2013)
INTRODUCTION: The descending branch of the lateral femoral circumflex artery is an option for coronary artery bypass grafting. OBJECTIVE: To evaluate the early patency and adaptation of lumen diameter using multidetector computed angiotomography. METHODS: Thirty-two patients were selected to undergo coronary artery bypass grafting using the descending branch of the lateral circumflex artery, the internal thoracic artery, and other grafts. Evaluations were carried out through high resolution computed tomography performed on the 7th and 90th postoperative day. Diameters of the descending branch of the lateral circumflex artery and the left internal thoracic artery were measured 3 cm before the distal anastomosis, in the middle portion, and 3 cm after the proximal anastomosis. Diameters were compared using paired t-test (P<0.05). RESULTS: Descending branch of the lateral femoral circumflex artery wDescending branch of the lateral femoral circumflex artery was used in 26 patients, as its use was not viable in six patients (18%). It was used as composite graft in all cases. The anterior descending branch was revascularized by the left internal thoracic artery in all cases. Patency rates of the descending branch of the lateral femoral circumflex artery were 96% and 92%, respectively. No occlusions were observed in the left internal thoracic artery (LITA) and no ischemic events were observed in the descending branch of the lateral circumflex. Descending branch of the lateral femoral circumflex artery increased the lumen diameter in the middle (P=0.001) and distal portions (P=0.006); the left internal thoracic artery (LITA) increased in the middle portion (P=0.001). CONCLUSION: Similar to the left internal thoracic artery, the descending branch of the lateral femoral circumflex artery showed high patency rate and positive luminal adaptation. This early evaluation confirms the descending branch of the lateral femoral circumflex artery as a potential alternative for grafting. Due to anatomical variations, preoperative femoral angiographic evaluation appears to be mandatory.